2006
DOI: 10.1534/genetics.105.050500
|View full text |Cite
|
Sign up to set email alerts
|

Substitution Mapping of dth1.1, a Flowering-Time Quantitative Trait Locus (QTL) Associated With Transgressive Variation in Rice, Reveals Multiple Sub-QTL

Abstract: A quantitative trait locus (QTL), dth1.1, was associated with transgressive variation for days to heading in an advanced backcross population derived from the Oryza sativa variety Jefferson and an accession of the wild rice relative Oryza rufipogon. A series of near-isogenic lines (NILs) containing different O. rufipogon introgressions across the target region were constructed to dissect dth1.1 using substitution mapping. In contrast to the late-flowering O. rufipogon parent, O. rufipogon alleles in the substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 68 publications
1
33
0
1
Order By: Relevance
“…This indicated that, in addition to pleiotropy, the effect of the QTL for seed yield could be a synthetic effect of several underlying tightly linked QTL of different yieldassociated traits. A previously mapped QTL may be dissected into several sub-QTL after subsequent fine mapping (Ashikari et al 2005;Thomson et al 2006;Christians and Senger 2007). Multiple indicator QTL were chosen for 14 pleiotropic QTL for seed yield, half of which involved QTL for seed yield in different environments.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that, in addition to pleiotropy, the effect of the QTL for seed yield could be a synthetic effect of several underlying tightly linked QTL of different yieldassociated traits. A previously mapped QTL may be dissected into several sub-QTL after subsequent fine mapping (Ashikari et al 2005;Thomson et al 2006;Christians and Senger 2007). Multiple indicator QTL were chosen for 14 pleiotropic QTL for seed yield, half of which involved QTL for seed yield in different environments.…”
Section: Discussionmentioning
confidence: 99%
“…However, a 15-cM genetic distance may cover 9 Mb and harbor 1800 genes in the rapeseed genome, and it is probable that at least two of these 1800 genes will respond to different environments. In contrast, one conventionally mapped QTL in rice and Arabidopsis may be subsequently ''modified'' into two sub-QTL with derived near-isogenic lines (NILs) (Monna et al 2002;Kroymann and Mitchell-Olds 2005;Thomson et al 2006). In this experiment, we used the default genetic distance 5 cM to define a QTL in a specific environment.…”
Section: Discussionmentioning
confidence: 99%
“…By combining this method with tests of advanced backcross progenies, several QTL were precisely localized in narrow genomic regions (Chen and Tanksley 2004;Thomson et al 2006). Furthermore, QTL isogenic recombinant analysis has been developed to speed up fine mapping of a QTL with a single population (Peleman et al 2005).…”
Section: Dissection Of the Genetic Modes Of Qtl Underlying Complex Qumentioning
confidence: 99%